Market Manifestation of Nonpublic Information Prior to Mergers: The Effect of Ownership Structure - Haw, In-Mu; Pastena, Victor S.; Lilien, Steven B. (The Accounting Review, 1990)
[In this article, we explore the ability of publicly available information to explain target firms' market "runups" prior to mergers and tender offers. Critics of the disclosure system argue that market runups before acquisition announcements indicate a failure of the disclosure system to guarantee equal access to information for all investors. However, the focus on acquisition announcement dates ignores that investors often have access to more timely sources of public information, including preliminary negotiation announcements, disclosures of the purchase of small blocks of stock, and published rumors. Thus, in assessing the market's use of non-public information, we concentrate on those runups that occur prior to the earliest possible public disclosure dates. Our emphasis on preliminary merger information parallels current legal and regulatory developments. Recent court decisions define preliminary merger negotiations as material information that is subject to Securities and Exchange Commission (SEC) disclosure laws. Also, the SEC now requires (with certain exemptions) the disclosure of preliminary merger negotiations in the Management Discussion and Analysis (MD&A) of forms 10-K and 10-Q. A second empirical question explored is whether market price movement prior to the release of merger information varies with firms' ownership structure (manager-controlled and owner-controlled firms). Since acquisitions often provide more attractive payoffs for owners as opposed to managers, ownership control structure may affect dissemination of firms' acquisition-related information. Therefore, we test whether presumed differences in target firms' information production are associated with distinct patterns of market runups. An event-type methodology is used for testing both questions. To test the event period, weekly residual returns are computed from CRSP for the period starting 20 weeks prior, and ending three weeks after, the first public disclosure date. For the 121 sample firms, the test statistics are based on the standardized average cumulative abnormal returns. Results indicate that substantial market activity occurs prior to what we could identify as the first public disclosure of any information about potential acquisition. This implies that such movements reflect nonpublic information or public information appearing in sources other than The Wall Street Journal and the Funk and Scott Index. We also found that market price runups occurred earlier for owner-controlled firms for both mergers and tender offers. The price runups were similar irrespective of whether the first public disclosure was definitive or hypothetical. Sensitivity tests indicate that the early price runups of owner-controlled firms are not explained by a few extreme values. The association between the timing of price runups and ownership structure reflects the expected differences in information production give firms' ownership control structure. This finding is consistent with the emphasis placed by the new auditing standards on firms' control environment including ownership structure.]